Numerical study of the influence of structural and mechanical parameters on the tensile mechanical behaviour of flax fibres. (July 2014) - Thuault, Anthony; Bazin, Jérôme; Eve, Sophie; Bréard, Joël; Gomina, Moussa
This paper presents the results of a numerical simulation of the ultimate flax fibre ( Linum usitatissimum ) tensile mechanical behaviour using finite element analysis. Experimental data were used to develop a numerical multilayer model of the flax fibre. Thus, the influence of some parameters, such as cell wall thicknesses, microfibrils angles (MFAs), biochemical composition and mechanical properties of the biochemical components, on the flax fibre tensile mechanical behaviour has been investigated. Results show that the typical stress–strain curve profile of the flax fibre could be due to the mechanical properties of hydrophilic components (hemicelluloses) and thus to the environmental conditions. A parameter sensitivity study reveals that ultrastructural parameters (hemicelluloses and cellulose Young's modulus) strongly influence the flax fibre mechanical behaviour and structural parameters (S2 cell wall layer MFA and thickness) significantly influence the fibre longitudinal Young's modulus. Thus, the knowledge of the fibre ultrastructure seems to be the key of the understanding of the flax fibre mechanical behaviour.